2022
DOI: 10.3386/w29806
|View full text |Cite
|
Sign up to set email alerts
|

The Wobbly Economy: Global Dynamics with Phase and State Transitions

Abstract: Gakuin U, and Nihon U. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research.NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…See, e.g. Cass and Stiglitz (1969) and Hirano and Stiglitz (2019). 67 Nothing, of course, was said about the stability of the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…See, e.g. Cass and Stiglitz (1969) and Hirano and Stiglitz (2019). 67 Nothing, of course, was said about the stability of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Behavior may depend on more than the expected value of a distribution, but on its entire shape. RE equilibria require that in such a situation, the individuals' beliefs about the shape of the distribution coincide with the observed (conditional) relative frequencies.16 Matters are even worse:Hirano and Stiglitz (2019) have shown that there may be an infinity of rational expectations trajectories. 17 Within a wide literature, seeBray (1982);Bray and Kreps (1987);Marcet and Sargent (1989) and the discussions in Honkapohja (1999, 2001).…”
mentioning
confidence: 99%